The impact of low-carbon pilot policies on enterprise environmental performance - Gao, Puying; Zhao , Juan (Transformations In Business & Economics, 2025)
This study seeks to examine the influence of low-carbon pilot policies on the corporate environmental performance of Chinese enterprises. The results reveal that in SOEs, the impact of low-carbon pilot policies is more significant, while in non-SOEs, the effect is relatively small. In heavily polluting enterprises, the influence of the pilot policies is more significant, while in non-heavy polluting enterprises, the impact is relatively small. The mentioned pilot policy provides a variety of mechanisms, including policy incentives, technical support, industry norms, social pressure, and market opportunities, thereby improving their environmental performance. In addition, it effectively alleviates financing constraints and provides financial support for enterprises to implement low-carbon technologies or innovations. Further analysis shows that green innovation and financing constraints have partial mediating effects in the process of improving corporate environmental performance through low-carbon pilot policies. This paper provides corresponding policy recommendations, including increasing policy support, strengthening the effect of policy implementation, and implementing differentiated low-carbon policies for different types of firms and different regions. Simultaneously, the paper also calls on enterprises to actively participate in the pilot policies to achieve sustainable development goals.